The Pathology of T Cells in Systemic Lupus Erythematosus - Anselm Mak; Nien Yee Kow (Journal of Immunology Research)
Systemic lupus erythematosus (SLE) is characterized by the production of a wide array of autoantibodies. Thus, the condition was traditionally classified as a “B-cell disease”. Compelling evidence has however shown that without the assistance of the helper T lymphocytes, it is indeed difficult for the “helpless” B cells to become functional enough to trigger SLE-related inflammation. T cells have been recognized to be crucial in the pathogenicity of SLE through their capabilities to communicate with and offer enormous help to B cells for driving autoantibody production. Recently, a number of phenotypic and functional alterations which increase the propensity to trigger lupus-related inflammation have been identified in lupus T cells. Here, potential mechanisms involving alterations in T-cell receptor expressions, postreceptor downstream signalling, epigenetics, and oxidative stress which favour activation of lupus T cells will be discussed. Additionally, how regulatory CD4+, CD8+, and γδ T cells tune down lupus-related inflammation will be highlighted. Lastly, while currently available outcomes of clinical trials evaluating therapeutic agents which manipulate the T cells such as calcineurin inhibitors indicate that they are at least as efficacious and safe as conventional immunosuppressants in treating lupus glomerulonephritis, larger clinical trials are undoubtedly required to validate these as-yet favourable findings.